Phase evolution in an MCrAlY coating during high temperature exposure - Costa, Chiara; Barbareschi, Emma; Guarnone, Paola; Borzone, Gabriella (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
MCrAlY (M = Ni and/or Co) coating systems are often applied on gas turbine blades and vanes to withstand the challenges of severe conditions. During service MCrAlY coatings are subjected to microstructural transformations that can be an indication of components service temperatures. The development of indirect methods to measure this parameter is of great concern in the gas turbine “world” due to the impossibility of direct measurements. In the present work the evolution of an MCrAlY coating applied on René80 by LPPS (Low Pressure Plasma Spray) technique has been studied in order to verify if it was possible to identify a microstructural indicator of the service temperature. The specimens were exposed for different lengths of time at test temperatures of 700 – 800 – 900 °C in order to characterize the phase evolution with time and temperature. Selective etching was employed for optical metallographic investigation. Scanning Electron Microscopy (SEM) observation combined with Electron Backscattered Diffraction (EBSD) and Energy Dispersive Spectroscopy (EDS) showed that the coating is composed of a γ- Co matrix, β-AlNi, σ-(Cr, Co), Cr carbide and Y-rich phases. Among these phases, the sigma phase resulted in a temperature – composition dependence that can be a useful tool for evaluating the local service temperature and modelling the residual lifetime.